The role of maladaptive emotion regulation in the bidirectional relation between sleep and depression in college students during the COVID-19 pandemic - Niu, Xinran; Snyder, Hannah R. (Anxiety, stress, and coping, 2023)
Background: Emotion regulation deficits are an outcome and risk factor for both insomnia and depression, suggesting that maladaptive emotion regulation might in part explain the bi-directional links between sleep and depression. The current study tests this hypothesis during the COVID-19 pandemic in emerging adult undergraduate students, a high-risk population for both depression and sleep disturbance. Methods: A sample of 154 undergraduate students completed a series of online questionnaires bi-weekly on sleep, depression, and emotion regulation strategies across eight weeks during the early days of the COVID-19 pandemic (April 2nd to June 27th, 2020). Results: Sleep disturbance and depression prospectively predicted one another across eight weeks, and both directions were mediated by maladaptive emotion regulation. However, sleep and depression failed to predict change in one another controlling for baseline measures, directly or via emotion regulation. Conclusions: The results suggest that maladaptive emotion regulation is a potential mechanism through which sleep disturbance and depression help maintain high levels of one another in college students during the COVID-19 pandemic. Therefore, emotion regulation deficits are potentially an important target for interventions to interrupt the sleep disturbance-depression cycle.